Improving Knowledge and Environmental Awareness Character in the Pancasila Student Profile Strengthening Project Using Low Carbon Emission Food Context in Junior High School - Azzahra, Cut Ina; Sulastri*, Sulastri; Johar, Rahmah; Mailizar, Mailizar; Haryani, Sri; Ishak, Muhammad Izzuddin Syakir (Jurnal IPA & Pembelajaran IPA, 2025)
Global warming is accelerating and is primarily driven by high greenhouse gas (GHG) emissions. The food sector is a significant contributor to carbon emissions, particularly food production and consumption. Therefore, it is crucial to instill knowledge about low-carbon emission foods in students early by integrating this topic into curricular activities, such as the project for strengthening the profile of pancasila students (P5). This study aims to evaluate the improvement in students' knowledge, attitudes, and behaviors regarding low-carbon emission foods before and after implementing the P5 project. A descriptive quantitative approach with a quasi-experimental method was employed in this study. The subjects consisted of 33 Year 7 students in Banda Aceh, Indonesia. The findings reveal that implementing the P5 project, grounded in low-carbon emission foods, significantly enhanced students' knowledge, attitudes, and environmentally conscious behaviors. The project provided students with theoretical knowledge and promoted behavioral change through practical experiences